The Microstructural and Hardness Changes of Tungsten Fiber after Au2+ Irradiation - Juan Du; Jialin Li; Chuan Wu; Qihang Zhang; Pan Wen; Jun Tang; Tianyu Zhao; Pinghuai Wang; Xiang Liu; Jiming Chen (Crystals, 2023)
Tungsten fiber-reinforced tungsten composite (Wf/W) material is considered a plasma-facing material (PFM) with good application prospects. Commercial tungsten wire (fiber) prepared through forging and drawing processes has excellent mechanical properties, as well as a very high recrystallization temperature due to the unique texture of it grain structure. Commercial tungsten fiber is the most proper reinforcement for Wf/W. The change in the properties of tungsten fiber because of neutron irradiation makes it inevitable for Wf/W to be used as PFMs. However, there is very little research on the change in the properties of tungsten fiber caused by neutron irradiation. In this work, we used heavy ion irradiation to simulate the displacement damage generated by neutron irradiation to explore the alteration of the properties of a commercial tungsten fiber caused by neutron irradiation. The investigated subject was tungsten fiber with a diameter of 300 μm. The irradiation source was 7.5 MeV Au2+, which generated a maximum displacement damage of 60 dpa at a depth of 400 nm, and the irradiation influenced depth was 1000 nm. Because of the irradiation, significant lattice distortion occurred within the tungsten fiber, resulting in the transition from (110) texture to (100) texture at the fiber’s cross-section. The results of the Schmidt factor and Taylor factor analysis indicate a decrease in the plasticity of the tungsten fiber after irradiation, but it did not completely lose its plasticity. The results of the nanoindentation test confirmed the radiation hardening. After irradiation, the hardness of the tungsten fiber increased by approximately 0.33 GPa, but this increase was relatively small compared to other tungsten-based materials. This indicates that commercial tungsten fiber is a low-cost and highly reliable reinforcement material for Wf/W composite materials.